On the optimization of direct methods for solving fredholm integral equations of the second kind with infinitely smooth kernels - Urumbaev, A. N. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
We give a direct method, optimal in $L_2$, for solving the Fredholm integral equation of the second kind with operators acting into the space of functions harmonic in a disk or into the space of functions that can be analytically extended to an infinite strip. The exact order of the error of this method is determined.